Design and simulation of a low noise PWM based phase synchronous inverter for microgrid - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (Institute of Electrical and Electronics Engineers, Inc., 2017)
A microgrid is a clear energy system consisting of demand management, storage, generation system and loads which are capable of operating in parallel or independently with the main power grid. There are some issues in the inverter circuit design which are, high frequency switching loss and noise. In addition, an electrostatic generator generates high voltage DC and low current. Any types of wave distortion or conversation losses of the inverter is a big challenged to use an electrostatic generator as an input energy source for the system. A pulse controller based switching circuit can be designed for increasing the inverter output efficiency. Herein an LCL filter has been designed to limit the THD to 3.2%. In this design, the switching frequency of the inverter is 1.65 kHz, the input supply of the inverter from an electrostatic generator of 10 kVdc, the output load of the inverter is a 100 Ω resistive load, the inverter output voltage is ±10 kVPP and the output supply frequency of the inverter is 50 Hz have been considered. The proposed inverter circuit has been simulated by MATLAB2014a. The conversion efficiency of the inverter without and with filter are observed as 66.2% and 96.8% respectively. The Phase synchronous error for each phase is approximately 50 degrees.